2009
DOI: 10.1007/s12011-009-8573-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lead on the Activities of Antioxidant Enzymes in Watercress, Nasturtium officinale R. Br.

Abstract: The aim of the present study is to evaluate the oxidative effects of lead with increased concentrations by the determination of antioxidant enzyme activities (superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), and ascorbate peroxidase (AP)) and lipid peroxidation levels in the stem and leaves of watercress (Nasturtium officinale R. Br.) which was exposed to lead acetate, Pb (CH3COOH)2 regime with concentrations of 0, 50, 100, 200, 250, and 500 mg/L Pb in a hydroponic culture. After 14 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…SOD is a key enzyme in protecting cells against oxidative stress and dismutases O − 2 to H 2 O 2 and O 2 (Alscher et al 2002). The observations made in the present study paralleled earlier studies reporting enhanced SOD activity under Pb stress (Choudhury & Panda 2005;Gupta et al 2009;Keser & Saygideger 2010;Kaur et al 2012b). A decline in CAT activity noticed in the present study suggested that this enzyme is not involved in providing protection against Pb toxicity in Z. mays root tips.…”
Section: Discussionsupporting
confidence: 85%
“…SOD is a key enzyme in protecting cells against oxidative stress and dismutases O − 2 to H 2 O 2 and O 2 (Alscher et al 2002). The observations made in the present study paralleled earlier studies reporting enhanced SOD activity under Pb stress (Choudhury & Panda 2005;Gupta et al 2009;Keser & Saygideger 2010;Kaur et al 2012b). A decline in CAT activity noticed in the present study suggested that this enzyme is not involved in providing protection against Pb toxicity in Z. mays root tips.…”
Section: Discussionsupporting
confidence: 85%
“…MDA content generally increases in plants treated with heavy metals. Increases in the level of MDA have been reported in aquatic plants such as G. densa (Cd), S. polyrhiza (Cd), Wolfia arrhiza (Cu, Pb), Potomogeton pusillus (Cu) and N. officinale (Pb) (Magdelena et al, 2009, Keser andSaygideger, 2010;Piotrowska et al, 2010;Yilmaz and Parlak, 2011). However, similar to results of this study, reduced MDA contents were reported in Cd-exposed Ceratophyllum, Hydrilla and Wolffia and Hg-exposed Bacopa monnieri plants (Dhir et al, 2004;Singh et al, 2006).…”
Section: Mda Amountsmentioning
confidence: 99%
“…APX has a more important role in the scavenging of ROS caused by oxidative stress and the affinity of this enzyme for H 2 O 2 is higher than CAT and POD (Gill and Tuteja, 2010). Stimulated APX activities were reported in C. demersum (Pb), G. densa (Cd), N. officinale (Pb), and W. arrhiza (Cd, Pb) (Mishra et al, 2006;Keser and Saygideger, 2010;Piortowska et al, 2010;Yilmaz and Parlak, 2011). Increased APX activity may be associated with activation of the enzymatic antioxidative system triggered by ROS.…”
Section: Apx Activitymentioning
confidence: 99%
“…SOD catalyzes the disproportionation of two O 2 -radicals to H 2 O 2 and O 2 (Iqbal et al 2010) and CAT and POX participate in the decomposition of H 2 O 2 . The role of GSH and GR in H 2 O 2 scavenging mechanisms in plant cells is well established in HalliwellAsada pathway/ascorbate-glutathione cycle (Bowler et al 1992;Keser and Saygideger 2010). GSH reacts chemically with a range of ROS, while enzyme-catalysed reactions link GSH to the detoxification of H 2 O 2 in the ascorbateglutathione cycle.…”
Section: Introductionmentioning
confidence: 99%